Hemopericardium caused by a mobile retained epicardial pacing wire after ventricular septal defect repair: A case report. Issue 39 (September 2016) - Hsu, Li-Sheng; Hsu, Jen-Te; Chen, Min-Lang; Liao, Chien-Lin
Abstract: Background: Epicardial pacing wires (EPWs) are commonly employed for diagnosis and treatment of arrhythmia in the acute phase after cardiac surgery. Although rare, retained EPWs may cause mild-to-catastrophic complications. The present case demonstrates hemopericardium caused by a mobile retained EPW. Methods: A 49-year-old woman presented to our emergency department with clinical signs of impending cardiac tamponade. She had undergone ventricular septal defect repair 7 years before this admission. An initial computed tomography (CT) scan revealed hemopericardium with suspicion of a possible intracardiac lesion. Review of the first and second CT scans, however, revealed a mobile retained EPW penetrating the pericardium in the first scan, which had moved out of the pericardium in the second scan. Results: Because cardiac injury by the EPW was suspected, the patient was transferred to another medical center for further treatment. Conclusion: According to our experience with this case, diagnosis may be incorrect if CT is unable to obtain decisive images of the mobile EPW at the correct time. Multiplanar reconstruction and volume rendering can increase diagnostic accuracy. In conclusion, if hemopericardium is present without clear etiology in a patient with a retained EPW, a nearby mobile EPW may be the cause.